The Characterization of Collagen Isolated from Red Snapper Fish Skin (Lutjanus sp.) by Hydroextraction Method with Different Concentration of Acid Solution - R. Rahardyan Prasetyo; Ahmad Shofy Mubarak; Eka Saputra; Juni Triastuti (Department of Aquaculture, 2023)
Collagen is a connective tissue protein that is mostly produced from cattle and pigs. The use of cows and pigs as the manufacture of collagen causes a disease case, among others are bovine spongiform encephalopathy and transmissible spongiform disease. One of the alternative materials in the isolation of collagen is the use of fish skin. The purpose of this study was to determine the effect of the concentration of acetic acid solution on the characteristics of red snapper collagen produced by the hydroextraction method and to determine the optimum concentration of acetic acid solution in the red snapper skin collagen isolation process using the hydroextraction method. This study was experimental with Completely Randomized Design (CRD) consisting of 3 acetic acid treatment: (P1) acetic acid with concentration 0,1 M; (P2) 0,15 M and (P3) 0,2 M. This study showed that the use of different acetic acid had a significant effect (p<0.05) on the yield parameters that is 1.72 – 2.46%, water content 11.12 – 12.8%, and protein content 83.66 – 84.81% and had no significant effect on the pH. The best treatment was P3 which use the higher concentration of acetic acid that produced higher yield 2.46% and protein content of 84.81%. P3 with concentration of acetic acid 0,2 M can be used for found the best result of characterization of collagen.